Impact of Season, Demographic and Environmental Factors on Salmonella Occurrence in Raccoons (Procyon lotor) from Swine Farms and Conservation Areas in Southern Ontario - Bondo, Kristin J; Pearl, David L; Janecko, Nicol; Boerlin, Patrick; Reid-Smith, Richard J; Parmley, Jane; Jardine, Claire M (PloS one, 2016)
Salmonella has been detected in the feces of many wildlife species, including raccoons (Procyon lotor), but little is known about the epidemiology of Salmonella in wildlife living in different habitat types. Our objective was to investigate demographic, temporal, and climatic factors associated with the carriage of Salmonella in raccoons and their environment on swine farms and conservation areas. Using a repeated cross-sectional study design, we collected fecal samples from raccoons and environmental samples (soil, manure pits, dumpsters) on 5 swine farms and 5 conservation areas in Ontario, Canada once every five weeks from May to November, 2011-2013. Salmonella was detected in 26% (279/1093; 95% CI 22.9-28.2) of raccoon fecal samples, 6% (88/1609; 95% CI 4.5-6.8) of soil samples, 30% (21/69; 95% CI 20.0-42.7) of manure pit samples, and 23% (7/31; 95% CI 9.6-41.0) of dumpster samples. Of samples testing positive for Salmonella, antimicrobial resistance was detected in 5% (14/279; 95% CI 2.8-8.3) of raccoon fecal, 8% (7/89; 95% CI 3.2-15.5) of soil, 10% (2/21; 95% CI 1.2-30.4) of manure pit, and 0/7 dumpster samples. Using multi-level multivariable logistic regression analyses, we found location type (swine farm or conservation area) was not a significant explanatory variable for Salmonella occurrence in raccoon feces or soil (p > 0.05). However, detection of Salmonella in raccoon feces was associated with rainfall, season, and sex with various interaction effects among these variables. We detected a variety of Salmonella serovars that infect humans and livestock in the feces of raccoons indicating that raccoons living near humans, regardless of location type, may play a role in the epidemiology of salmonellosis in livestock and humans in southwestern Ontario.
Keywords: demografie; Feces; mývalové; Male; životní prostředí; mikrobiologie životního prostředí; Raccoons; Demography; Environment; Drug Resistance, Bacterial; Salmonella; Microbial Sensitivity Tests; mužské pohlaví; Environmental Microbiology; salmonelová infekce u zvířat; Salmonella Infections, Animal; Animals; lidé; farmy; ženské pohlaví; roční období; Seasons; Humans; bakteriální léková rezistence; zvířata; mikrobiální testy citlivosti; Farms; Ontario; Female; feces